TECHNOLOGY FOR IMPROVING THE PROFESSIONAL SKILLS OF A TEACHER EDUCATOR - Reymbergenova Dilnoza (Bright Mind Publishing, 2025)
The integration of technology in teacher education has significantly enhanced the professional development of teacher educators. Digital tools such as online learning platforms, artificial intelligence, virtual and augmented reality, and digital collaboration tools enable educators to refine their teaching methodologies, personalize learning, and engage in continuous professional growth. Despite challenges such as digital literacy and accessibility, technological advancements provide innovative solutions for improving teacher training. This article explores various digital resources that support teacher educators in adapting to modern educational demands and fostering effective teaching practices.
Keywords: Teacher educator, professional development, educational technology, artificial intelligence, virtual learning, digital tools.